FACTORS AFFECTING CRITICAL AND HOLISTIC THINKING IN ISLAMIC EDUCATION IN INDONESIA: SELF-CONCEPT, SYSTEM, TRADITION, CULTURE. (LITERATURE REVIEW OF ISLAMIC EDUCATION MANAGEMENT) - Ismail, Ismail; Ali, Hapzi; Anwar Us, Kasful (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Based on previous research or relevant research, it certainly serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence critical and holistic thinking in Islamic education in Indonesia, namely: Self-Concept, Systematics, Tradition, and Culture, which is a form of qualitative research and literature study or library research on Islamic Education Management. The results of this literature review article show that: (1) Self-concept influences critical and holistic thinking in Islamic education; (2) System influences critical and holistic thinking in Islamic education; (3) Tradition influences critical and holistic thinking in Islamic education;